2019
DOI: 10.2528/pierb18120406
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Calculation of the Power Transfer and Efficiency in Resonator Arrays for Inductive Power Transfer

Abstract: This paper studies the power transfer characteristics of a resonator array for inductive power transfer by means of the accurate analytical solution of its circuit model. Through the mathematical inversion of a tridiagonal matrix, it is possible to obtain closed-form expressions for the current in each resonator and consequently expressions for the power transfer and efficiency of the system. The method can be applied to a resonator array powering a load at the end of the array or a receiver facing the array a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In the given hypotheses, the maximum power gain, and the corresponding currents (up to an arbitrary factor) can be determined by solving (12) with the constraint…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In the given hypotheses, the maximum power gain, and the corresponding currents (up to an arbitrary factor) can be determined by solving (12) with the constraint…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…It can be observed that by (12) it is also possible to determine the maximum power gain when the role of the ports is interchanged, that is when the power supply is provided at ports b 1 , . .…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most of the existing WPT systems, usually, only one load is powered via the magnetic or electric field [6][7][8][9]. Recently, more and more publications investigated the WPT system with multiple loads [10][11][12][13][14][15][16][17][18]. In [10], a WPT system with two receivers (Rxs) was designed, where the two receiving coils are decoupled by adjusting the winding direction of turns.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the gate drivers are placed near these IGBTs, the WPT system should have the capability to transfer power over a long distance. The repeater coil structure [14, 15] could be a good solution because the coils can not only increase the power transfer distance but also be connected to multiple loads. In [16], the repeater coils were adopted to power multiple loads.…”
Section: Introductionmentioning
confidence: 99%